Writing robotics : Africa vs Asia. - Mwanaka, Tendai R. (Multi-disciplinary series, 2020)
Writing Robotics, Africa Vs Asia Vol 2 follows Writing Language, Culture and Development, Africa vs Asia, Vol 1. Writing Robotics features 18 writers and poets from the two regions, Asia and Africa collaborating around the issue of Robots, in whatever form. From the traditional African robotics science, to the latest robots and the imagined robots of tomorrow, how the two regions Africa and Asia are coming to terms with the oncoming Robotics revolution, the so-called 4th industrial revolution. The book serves to encourage rather than to scare the inhabitants of these regions to embrace the revolution, and to show them robots are already a part of us as we are a part of them.